Samson and Delilah - Benagh, Christine L.; Bullock, Harvey (Nashville : Abingdon Press, 1986)
Derek, Margo, and Moki once again go back in time and meet Samson, who is engaged in constant struggle with the Philistines for freedom for the Israelites.
Keywords: Samson -- (Biblical judge) -- Juvenile fiction; Delilah -- (Biblical figure) -- Juvenile fiction; Samson -- (Biblical judge) -- Fiction; Delilah -- (Biblical figure) -- Fiction; Time travel -- Fiction